2007
DOI: 10.1158/1078-0432.ccr-06-2260
|View full text |Cite
|
Sign up to set email alerts
|

Current Development of Clinical Inhibitors of Poly(ADP-Ribose) Polymerase in Oncology

Abstract: Poly(ADP-ribose) polymerase (PARP) is a nuclear enzyme that signals the presence of DNA damage by catalyzing the addition of ADP-ribose units to DNA, histones, and various DNA repair enzymes and by facilitating DNA repair. PARP has been gaining increasing interest as a therapeutic target for many diseases and especially for cancer. Inhibition of PARP potentiates the activity of DNA-damaging agents, such as alkylators, platinums, topoisomerase inhibitors, and radiation in in vitro and in vivo models. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
214
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(222 citation statements)
references
References 67 publications
1
214
0
7
Order By: Relevance
“…Olaparib has also been reported to enhance the effects of conventional cytotoxic agents in homologous recombination-defective cells (19)(20)(21). The suppression of homologous recombinational repair due to RAD51C deficiency is associated with disturbed RAD51 foci formation at irradiation-induced DSB sites (14).…”
Section: Olaparib Sensitizes Cancer Cells To Ionizing Radiationmentioning
confidence: 99%
“…Olaparib has also been reported to enhance the effects of conventional cytotoxic agents in homologous recombination-defective cells (19)(20)(21). The suppression of homologous recombinational repair due to RAD51C deficiency is associated with disturbed RAD51 foci formation at irradiation-induced DSB sites (14).…”
Section: Olaparib Sensitizes Cancer Cells To Ionizing Radiationmentioning
confidence: 99%
“…The branching ADP-ribose polymers provide a scaffold for the assembly of repair proteins and the initiation of the complex repair reaction (Haince et al, 2005). Chemo-and radiosensitization by PARP inhibition has been the subject of many reviews (Haince et al, 2005;Plummer, 2006;Plummer and Calvert, 2007;Ratnam and Low, 2007;Lord and Ashworth, 2008). A review of the original research reports indicates that although chemo-and radiotherapy can synergize with PARP inhibitors (PARPi), the assessment of the resulting cellular responses may be limited if clonogenic survival or growth inhibition are chosen as end points (Calabrese et al, 2003(Calabrese et al, , 2004Curtin et al, 2004).…”
Section: Arrest/senescencementioning
confidence: 99%
“…PARP is involved in the recognition and repair of RHPS4-induced telomere damage We next evaluated the consequences of PARP inhibition in RHPS4-treated cells by using both PARP1-specific interference RNA and GPI 15427 (GPI), a wellestablished PARP inhibitor already characterized by our group and the analog (GPI 21016) of which is now in clinical trial (Tentori et al, 2006;Ratnam and Low, 2007). The deconvolution analysis, used to examine the formation of telomere dysfunction induced foci, revealed that either siPARP1 or GPI alone did not induce damage (Figures 3a-c).…”
Section: Parp Inhibition Increases the Efficacy Of Telomere-based Thementioning
confidence: 99%
“…In addition, tumors with DNA repair defects, such as those arising from patients with BRCA mutations, are more sensitive to PARP inhibition, suggesting that PARP inhibitors may be particularly useful for the treatment of cancer with BRCA mutations (Farmer et al, 2005). On the basis of the promising data on preclinical models, different companies have now initiated oncology clinical trials with PARP inhibitors, ranging in stages from phase 0 to phase 2 (Ratnam and Low, 2007).…”
Section: Introductionmentioning
confidence: 99%